German-Czech Cultural Standards in Business Environment - Jurečková, Alena (2024)
This bachelor's thesis focuses on cultural standards between Germany and the Czech Republic in a business environment. The thesis aims to identify critical differences between German and Czech business cultures and working attitudes and to propose recommendations for improving cooperation between the two countries. The research combines the theoretical basis of studies by Geert Hofstede and Fons Trompenaars with data collected through interviews with German and Czech respondents.